2000
DOI: 10.1080/10245332.2000.11746528
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Metabolites in Sickle Cell Anemia Patients after Oral Administration of Hydroxyurea

Abstract: The mechanism of action of hydroxyurea (HU) in decreasing the frequency of pain crisis in sickle cell disease (SCD) has not been fully elucidated. In vitro and in vivo studies suggest that nitric oxide (NO), a potent vasodilator, may partly be responsible for the beneficial effect of HU. This study was designed to determine the effect of oral administration of HU on plasma levels of NO metabolites (NO(x) ) in sickle cell patients (SCP). The results indicate that during steady-state plasma levels of NO(x) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 17 publications
1
36
0
9
Order By: Relevance
“…HU is believed to be a chemical donor of NO, 29,30 a potent vasodilator, and NO seems to provide a variety of beneficial effects in SCA: (i) low-dose inhalation of NO increases the oxygen affinity of sickle red cells both in vivo and in vitro, 31 (ii) NO inhalation at 20 ppm seems to provide a rapid protection against severe hypoxic stress in a transgenic mice model for SCD, 32 (iii) in SCA patients with ACS, inhaled NO improves ventilation-perfusion matching 33 and (iv) SCA patients with elevated levels of NO metabolites report lower pain scores. 34 NOS tightly regulates the NO expression in endothelial cells. We did not observe any alteration in the level of NO metabolites or changes in the endothelial expression of NOS either at transcriptional or protein level in HU-treated ECs, which suggests that the HU effect may not be mediated by this pathway.…”
Section: Effect Of Hu On Endothelial Cell Cycle Changesmentioning
confidence: 99%
“…HU is believed to be a chemical donor of NO, 29,30 a potent vasodilator, and NO seems to provide a variety of beneficial effects in SCA: (i) low-dose inhalation of NO increases the oxygen affinity of sickle red cells both in vivo and in vitro, 31 (ii) NO inhalation at 20 ppm seems to provide a rapid protection against severe hypoxic stress in a transgenic mice model for SCD, 32 (iii) in SCA patients with ACS, inhaled NO improves ventilation-perfusion matching 33 and (iv) SCA patients with elevated levels of NO metabolites report lower pain scores. 34 NOS tightly regulates the NO expression in endothelial cells. We did not observe any alteration in the level of NO metabolites or changes in the endothelial expression of NOS either at transcriptional or protein level in HU-treated ECs, which suggests that the HU effect may not be mediated by this pathway.…”
Section: Effect Of Hu On Endothelial Cell Cycle Changesmentioning
confidence: 99%
“…Importantly, preclinical and clinical studies demonstrated that hydroxyurea increases the plasma level of NO species and stimulates a cGMP-signaling pathway. 5,6,8,9 As seen in SCD mice after intravenous infusion of hydroxyurea, 9 plasma NOx levels were also elevated after oral administration of hydroxyurea to SCD mice. Although combination therapy with hydroxyurea and ARQ 092 showed beneficial effects on acute vasoocclusive events and survival in TNF-α-challenged SCD mice, the plasma NOx levels increased by hydroxyurea treatment seemed to be slightly decreased by the dual therapy (hydroxyurea versus hydroxyurea + ARQ 092Ȩ ffect of ARQ 092 on acute vaso-occlusion in SCD haematologica | 2017; 102 (2) 257 Figure 7.…”
Section: Discussionmentioning
confidence: 86%
“…[5][6][7] Consistently, in vivo studies showed that intravenous infusion of hydroxyurea increases the level of plasma NO metabolites (NOx) and has beneficial effects on vaso-occlusive events in Berkeley mice, a model of SCD. 8,9 However, SCD patients on hydroxyurea therapy often suffer from vaso-occlusive crises, suggesting that a novel or supplemental therapy is required.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, it was shown that iNOS inhibition significantly limits tissue ischemia-reperfusion injury in the liver and kidneys [10,11]; however, inhibition of iNOS attenuated ischemia-reperfusion injury in the rat heart [12] and did not affect ischemia-reperfusion injury in the rat lung [13]. Increased levels of iNOS expression were shown in the kidneys of transgenic mice [9], but Nath et al [14] reported the lack of upregulation of iNOS in the intrarenal vasculature and increased expression of iNOS in the [15][16][17] and in vitro [18]. It was reported that NOS activity plays a role in stimulating production of NO x .…”
Section: Introductionmentioning
confidence: 99%